Synthesis of new functionalized triarylmethanes via Suzuki cross-coupling and Heck-type vinylation reactions - Mohammadiannejad, Kazem; Hosseini, Raziyeh; Ranjbar-Karimi, Reza (Comptes Rendus. Chimie, 2020)
A novel class of triarylmethanes (TRAMs) containing one or two biaryl moieties was synthesized efficiently through the $Pd(PPh_{3})_{4}$-catalyzed Suzuki–Miyaura cross-coupling reaction of brominated TRAMs with arylboronic acid derivatives. We also demonstrate that brominated TRAMs can be efficiently functionalized via a one-pot, two-step Pd-catalyzed Heck-type process. This protocol provides convenient access to diverse vinylated TRAMs that are generally not obtained by using the common synthetic methods for TRAMs.